1996
DOI: 10.1002/(sici)1096-9861(19961021)374:3<467::aid-cne10>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin accumulates at specific plasmalemma loci during neuronal maturation in vitro

Abstract: The distribution of glycine receptor (GlyR)-associated gephyrin has been investigated in rat spinal cord neurons maintained in vitro by means of immunocytochemical techniques. Gephyrin, which is crucial for the stabilization of postsynaptic GlyR microdomains, is present in mature neurons at postsynaptic differentiations. With immunofluorescence, discontinuous patches of gephyrin were detected within the neuronal soma of spinal cord neurons on the 1st day after plating. Subsequently, gephyrin was present at mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…In cultured neurons, endogenous gephyrin is mostly associated with the MAP2-positive somato-dendritic compartment from day 5 in vitro (DIV5) onward (Colin et al, 1996) and is mainly localized at subsynaptic and perisynaptic regions (Lorenzo et al, 2004). To study a potential role of neuronal activity and Ca 2+ increase in the sorting of gephyrin between axons and dendrites, we aimed to use neuronal cultures at later stages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cultured neurons, endogenous gephyrin is mostly associated with the MAP2-positive somato-dendritic compartment from day 5 in vitro (DIV5) onward (Colin et al, 1996) and is mainly localized at subsynaptic and perisynaptic regions (Lorenzo et al, 2004). To study a potential role of neuronal activity and Ca 2+ increase in the sorting of gephyrin between axons and dendrites, we aimed to use neuronal cultures at later stages.…”
Section: Resultsmentioning
confidence: 99%
“…In young cultured neurons, gephyrin has been detected in axons (Craig et al, 1996), however at later stages, it is mainly restricted to the somatodendritic compartment (Colin et al, 1996). Application of nocodazole or microinjection of KIF5-specific antibodies interfered with the post-Golgi delivery of gephyrin into dendrites of mature cultured hippocampal neurons (Maas et al, 2009), indicating that gephyrin uses microtubule-dependent kinesin transport to reach the cell periphery.…”
Section: Introductionmentioning
confidence: 99%
“…This apparent contradiction resulted from the presence of an intracellular pool of gephyrin detected with the VeGe chimera, but which was not well detected with immunofluorescence in nontransfected cells with the mAb7a antibody used in these experiments (Dumoulin et al, 1999;Danglot et al, 2003;Hanus et al, 2004). However, this pool can be visualized unambiguously in nontransfected cells under the electron microscope (Seitanidou et al, 1992;Colin et al, 1996Colin et al, , 1998 or using another commercially available mAb (BD Biosciences, San Diego, CA) (data not shown).…”
Section: Synaptic Targeting Of Fluorescent Protein-gephyrin Chimeramentioning
confidence: 99%
“…Originally, GlyRs (Bechade et al, 1996) and the GlyR-interacting protein gephyrin (Seitanidou et al, 1992; Colin et al, 1996) were identified at intracellular sites in neurons, and depolymerization of microtubules dispersed the subcellular accumulation of both proteins (Kirsch and Betz, 1995). A direct association of gephyrin with the light chains Dlc-1/Dlc-2, components of the microtubule-dependent dynein motor, suggested that microtubule transport might be involved in the subcellular localization of these factors (Fuhrmann et al, 2002) (Figure 1).…”
Section: Transport To and From Synaptic Regionsmentioning
confidence: 99%